Haemodynamic changes after prolonged water immersion - Boussuges, A.; Gole, Y.; Mourot, L.; Jammes, Y.; Melin, B.; Regnard, J.; Robinet, C. (Journal of Sports Sciences, 2009)
Thermoneutral water immersion increases cardiac preload and changes the neuroendocrine settings of blood volume regulation. The resulting marked diuresis may lead to significant haemodynamic changes after the end of a prolonged water immersion. Ten volunteers underwent 6 h of complete thermoneutral water immersion. Changes in cardiovascular status were assessed 1 h and 16 h after water immersion. Haemodynamic changes were assessed by Doppler echocardiography. Arterial wall distensibility was estimated by pulse wave velocity analysis. One hour after water immersion, mean weight loss was 1.78 kg and urine volume amounted to 1.5 litres. Echocardiographic measurements evidenced a significant decrease in dimensions of the left cardiac chambers and inferior vena cava. The decreased cardiac preload was paralleled by a lower stroke volume and cardiac output. A peripheral vasoconstriction associated with a relative decrease in the lower limb blood flow was evidenced by an increase in carotid-pedal pulse wave velocity and by a decrease in ankle brachial index. Sixteen hours after water immersion, cardiac preload and cardiac output remained below baseline values and peripheral vascular tone was still higher than at baseline. Marked haemodynamic changes had not returned to baseline 16 h after water immersion. There is a need to design fluid-replacement protocols to improve this recovery.